Spermatological characters of the aspidogastrean Aspidogaster limacoides Diesing, 1835 - Levron, Céline; Suchanová, Eva; Poddubnaya, Larisa; Oros, Mikulás; Scholz, Tomás (Parasitology research, 2009)
Using transmission electron microscopy, spermiogenesis and the spermatozoon ultrastructure are described in Aspidogaster limacoides (Aspidogastrea, Aspidogastridae), from two cyprinid fishes, Abramis sapa and Blicca bjoerkna, from eastern Slovakia and north-western Russia. Results of the present investigation permit, for the first time in Aspidogastrea, to describe general pattern of spermiogenesis and the organization of the spermatozoon in this presumably the most basal group of parasitic flatworms (Neodermata). Spermiogenesis starts by the formation of a zone of differentiation characterized by long striated rootlets, two centrioles giving rise to flagella, and intercentriolar body composed of different electron-dense plates. Later, a flagellar rotation followed by a proximodistal fusion of the flagella with the cytoplasmic extension takes place. Beside the possession of elements typical of Neodermata, such as two axonemes of the 9 + '1' trepaxonematan pattern, nucleus, mitochondrion and cortical microtubules, the mature spermatozoon of A. limacoides exhibits characteristics unique in Aspidogastrea: (a) a long undulating membrane, (b) an electron-dense zone, and (c) a lamellate body. The terminology and structure of different typical elements of Aspidogastrea are discussed. It is interesting to note that the long undulating membrane and a continuous row of cortical microtubules have already been described in polyopisthocotylean monogeneans, which can be a case of convergence unless future phylogenetic studies confirm relatedness of these groups.
Keywords: buněčné jádro; Russia; Rusko; mužské pohlaví; Organelles; transmisní elektronová mikroskopie; Cyprinidae; Slovakia; Cell Nucleus; Slovenská republika; zvířata; Spermatogenesis; organely; Microscopy, Electron, Transmission; Trematoda; Spermatozoa; spermatogeneze; spermie; Male; Animals